INCLUSIVE EDUCATION IN MADRASAH: CHALLENGES AND IMPLEMENTATION STRATEGIES - Suaidi; Ulfah Umurohmi; Runik Machfiroh; Rahma Helal Al_ Jbour (Adisam Publisher, 2024)
Inclusive education in the madrasah is an increasingly important topic in today's educational context. This article discusses the challenges and strategies of implementing inclusive education in madrasah. The method of research carried out is the study of literature by searching for literature that fits the context of research. The research finds that the main challenges facing inclusive education in the madrasah are related to a lack of understanding and awareness of inclusive education, as well as a shortage of adequate resources and facilities. To address these challenges, implementation strategies are needed, including improved understanding through training for educators and collaboration between madrasas, parents, and associated institutions. Then, another challenge is the adoption of individualization and differentiation learning approaches also needed to support student diversity. By identifying challenges and implementing appropriate implementation strategies, inclusive education in the madrasah can be more effective and successful in supporting the learning success of all students.